The United States–China Trade War and Its Implications for Rupiah Fluctuations and Foreign Investment Inflows in Indonesia - Fitri, Salsabila Dwi; Ananta, Yorasakhi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
The Role of the United States–China Trade War and Rupiah Exchange Rate Fluctuations on Foreign Investment Inflows in Indonesia is a scientific article of literature study in the scope of international law and political economy. The purpose of this article is to build a hypothesis of the role between variables that will be used in further research. The research objects are online libraries, Google Scholar, Mendeley, and other academic online media. The research method uses a library research approach sourced from e-books and open access e-journals. The analysis is carried out descriptively qualitatively. The results of this article show that: 1) The United States–China trade war plays a role in foreign investment inflows in Indonesia through changes in the direction of global investment flows; and 2) Rupiah exchange rate fluctuations play a role in foreign investment inflows through increasing perceptions of domestic economic risk.